Pemberian Edukasi Manajemen Stres pada Deteksi Dini Kanker Payudara di RW 09 Kelurahan Margahayu Utara Kecamatan Babakan Ciparay Bandung - Siagian, Ira Ocktavia; Sianipar, Imelda; Fuadah, Fahmi; Tumbol, Monika; Astutik, Windu (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background: Community service carried out at RW 09 Margahayu Utara Village, Babakan Ciparay Bandung District through community service activities which are an annual agenda for lecturers and students of the Immanuel Bandung Health Institute. In 2022, the Immanuel Bandung Institute of Health is concentrating on community service activities in Margahayu Utara Village and Babakan Ciparay Village, Babakan Ciparay District. The target of this community service group activity is the community in RW.09, North Marhagayu Village. Purpose:  the purpose of community service is to increase the knowledge of the RW.09 community, namely stress management education on early detection of breast cancer in RW. 09 Kelurahan Margahayu Utara, as well as knowing about education in health education. Methods: This activity was carried out in RW.09 Kel. Margahayu Utara by using a community empowerment approach. Results: The communities in question are the people of RT 1, RT 2, RT 3, RT 4, RT 5 and RT 6 Margahayu Utara, Babakan Ciparay District. The form of health counseling provided is through the provision of material with lectures, discussions and demonstrations. Based on the evaluation in the form of pre-test and post-test, it was found that there was an increase in knowledge of RW.09 from 50% to 90%. This health education also provides enrichment on good stress management for the community and health cadres in RW.09, Babakan Ciparay District.